2015
DOI: 10.4238/2015.may.11.20
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate peroxidase from Jatropha curcas enhances salt tolerance in transgenic Arabidopsis

Abstract: ABSTRACT. Ascorbate peroxidase (APX) plays a central role in the ascorbate-glutathione cycle and is a key enzyme in cellular H 2 O 2 metabolism. It includes a family of isoenzymes with different characteristics, which are identified in many higher plants. In the present study, we isolated the APX gene from Jatropha curcas L, which is similar with other previously characterized APXs as revealed by alignment and phylogenetic analysis of its deduced amino acid sequence. Real-time qPCR analysis showed that the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Interestingly, Gomez et al [ 42 ] demonstrated that a long-term (6- or 9-day) infestation of cotton ( Gossypium hirsutum L.) leaves with the cotton aphids ( Aphis gossypii G.) did not influence significant alternations in total activity of APX relative to the non-stressed control. Moreover, it has been well documented that overexpressed or silenced APX mutants of the several plant species displayed circumstantial alternations in their growth and development, ROS homeostasis, signaling networks, efficiency of the antioxidative machinery and/or defensive responses to diverse stressing factors [ 38 , 43 ]. Exemplarily, it has been uncovered that the transgenic lines of A. thaliana overexpressing APX gene from Jatropha curcas L., exhibited an elevated salt tolerance in relation to the WT plants [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Gomez et al [ 42 ] demonstrated that a long-term (6- or 9-day) infestation of cotton ( Gossypium hirsutum L.) leaves with the cotton aphids ( Aphis gossypii G.) did not influence significant alternations in total activity of APX relative to the non-stressed control. Moreover, it has been well documented that overexpressed or silenced APX mutants of the several plant species displayed circumstantial alternations in their growth and development, ROS homeostasis, signaling networks, efficiency of the antioxidative machinery and/or defensive responses to diverse stressing factors [ 38 , 43 ]. Exemplarily, it has been uncovered that the transgenic lines of A. thaliana overexpressing APX gene from Jatropha curcas L., exhibited an elevated salt tolerance in relation to the WT plants [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been well documented that overexpressed or silenced APX mutants of the several plant species displayed circumstantial alternations in their growth and development, ROS homeostasis, signaling networks, efficiency of the antioxidative machinery and/or defensive responses to diverse stressing factors [ 38 , 43 ]. Exemplarily, it has been uncovered that the transgenic lines of A. thaliana overexpressing APX gene from Jatropha curcas L., exhibited an elevated salt tolerance in relation to the WT plants [ 43 ]. Similarly, A. thaliana transformants overexpressing the two transgenes: APX and superoxide dismutase ( SOD ), derived from Rheum australe Don and Potentilla atrosanguinea Lodd., accordingly, characterized with an enhanced salt stress tolerance, increased expression of the genes involved in biosynthesis of the secondary cell wall and encoding the numerous transcription factors (e.g., C3Hs, MYBs, NACs and WRKY) in comparison with the control plants [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of excessive ROS and H 2 O 2 may cause cellular injury [59]. Ascorbate peroxidase catalyzes the conversion of H 2 O 2 to H 2 O and O 2 , and scavenges ROS to protect against the toxic effects of ROS accumulation in higher plants [60]. Previous research has shown that AtAPX1 performs an important function in the drought stress response by protecting chloroplasts from oxidative damage in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…In the enzymatic system, SOD constitutes the first line of defense against ROS by dismutating O 2 -to H 2 O 2 . Subsequently, H 2 O 2 is broken down by CAT, POD, and APX (Chen et al, 2015). We found that POD levels had significantly increased in MsPOD transgenic Arabidopsis plants compared to those in WT plants, but CAT levels had not changed.…”
Section: Discussionmentioning
confidence: 77%